Identification and Control of Coral Ardisia (Ardisia crenata): A Potentially Poisonous Plant. - Brent A. Sellers; Sarah Lancaster; Kenneth A. Langeland; Jason A. Ferrell; Michael Meisenberg; Joseph Walter (EDIS, 2013)
Coral ardisia, also known as coral berry, spice berry, and scratchthroat, was introduced to Florida in the early 1900′s for ornamental purposes. Since then, it has escaped cultivation, and it is found in hardwood hammocks and other moist, natural-wooded areas and grazing lands. Although there is no published literature supporting the theory that coral ardisia is toxic, it is suspected that the berries and/or foliage are poisonous to livestock, pets, and humans. This 3-page fact sheet was written by B. A. Sellers, Sarah Lancaster, K. A. Langeland, J.A. Ferrell, Michael Meisenberg, and J. Walter, and published by the UF Department of Agronomy, November 2013. http://edis.ifas.ufl.edu/ag281